Digital tomosynthesis parallel imaging computational analysis with Shift and Add and Back Projection reconstruction algorithms. (7th February 2011) - Chen, Ying; Balla, Apuroop; Rayford II, Cleveland E.; Zhou, Weihua; Fang, Jian; Cong, Linlin
Digital tomosynthesis is a novel technology that has been developed for various clinical applications. Parallel imaging configuration is utilised in a few tomosynthesis imaging areas such as digital chest tomosynthesis. Recently, parallel imaging configuration for breast tomosynthesis began to appear too. In this paper, we present the investigation on computational analysis of impulse response characterisation as the start point of our important research efforts to optimise the parallel imaging configurations. Results suggest that impulse response computational analysis is an effective method to compare and optimise imaging configurations.